A NEW SPECIES OF DRYPETES (PUTRANJIVACEAE) FROM THE CENTRAL AFRICAN REPUBLIC - HARRIS, D. J .; WORTLEY, A. H. (Edinburgh Journal of Botany, 2006)
The new species Drypetes bakembei D.J.Harris & Wortley (Putranjivaceae), from tropical forest in the south west Central African Republic, is described and illustrated.
Keywords: Central African Republic; Drypetes; Dzanga-Sangha Reserve; Malpighiales; Putranjivaceae